Diagnosis of infective endocarditis using echocardiography. Issue 38 (September 2019) - Yuan, Xin-chun; Liu, Ming; Hu, Jia; Zeng, Xi; Zhou, Ai-yun; Chen, Li
Abstract : Abstract: The aim of this study was to evaluate the application of transthoracic echocardiography for the diagnosis of infective endocarditis (IE) to provide a basis for the better treatment of IE. From October 2016 to October 2018, 87 consecutive patients with IE at our hospital were selected for this study. All the patients were subjected to transthoracic echocardiography. The morphology, structure, activity, and closure of the patients' heart valves were observed for vegetation identification, and the size, number, location, morphology, and echo intensity of vegetation, as well as degree of valve involvement, were determined. The 87 patients investigated in this study included 38 cases of congenital heart disease, 27 cases of nonrheumatic valvular heart disease, 12 patients who underwent valve surgery, 5 cases of rheumatic valvular heart disease, and 5 patients with no obvious signs of heart disease. The most common clinical manifestations were heart murmur in 80 cases and fever in 60 cases. The most common complications were heart failure in 35 cases, followed by organ embolism in 12 cases. There were 36 cases of positive blood cultures, including 26 cases of Gram-positive cocci and 10 cases of Gram-negative bacilli. Echocardiography showed aortic valve involvement in 37 cases, mitral valve involvement in 34 cases, tricuspid valve involvement in 10 cases, pulmonary valve involvement in 2 cases, and the involvement of an artificial valve in 5 cases. Twenty-six of these cases showed multiple valve involvement, and 20 patients exhibited serious complications. No significant differences were found between echocardiography and actual surgical observations with respect to their accuracy in detecting the size, number, and location of vegetation in the 69 patients who underwent surgery ( P  > .05). Echocardiography could detect the occurrence of severe complications, namely, the rupture of chordae tendineae, valve prolapse, valve perforation, and paravalvular abscess, and no significant difference in diagnostic accuracy was found between echocardiography and surgical observations ( P  > .05). Transthoracic echocardiography can rapidly and accurately detect IE vegetation and its complications and has important clinical value for guiding clinical treatment and determining prognosis.